Dynasore Alleviates LPS-Induced Acute Lung Injury by Inhibiting NLRP3 Inflammasome-Mediated Pyroptosis - Shan M; Wan H; Ran L; Ye J; Xie W; Lu J; Hu X; Deng S; Zhang W; Chen M; Wang F; Guo Z (Dove Medical Press, 2024)
Mengtian Shan,1 Huimin Wan,1 Linyu Ran,1 Jihui Ye,1 Wang Xie,2 Jingjing Lu,1 Xueping Hu,1 Shengjie Deng,1 Wenyu Zhang,1 Miao Chen,3 Feilong Wang,1 Zhongliang Guo1,4 1Department of Pulmonary and Critical Care Medicine, Shanghai East Hospital, School of Medicine, Tongji University, Shanghai, People's Republic of China; 2Department of Respiratory Medicine, The First Affiliated Hospital of USTC, Division of Life Sciences and Medicine, University of Science and Technology of China, Hefei, Anhui, People's Republic of China; 3Department of Emergency, The First Affiliated Hospital of Hainan Medical University, Haikou, Hainan, People's Republic of China; 4Department of Respiratory Medicine, Ji'an Hospital, Shanghai East Hospital, Shanghai, Jiangxi, People's Republic of ChinaCorrespondence: Zhongliang Guo; Feilong Wang, Shanghai East Hospital, School of Medicine, Tongji University, 150st Jimo Road, Pudong, Shanghai, 200092, People's Republic of China, Tel +86-21-38804518, Fax +86-21-20334513, Email drguozhl@163.com; wang_feilong@tongji.edu.cnBackground: Acute lung injury (ALI) and acute respiratory distress syndrome (ARDS) are clinically severe respiratory disorders without available pharmacological therapies. Dynasore is a cell-permeable molecule that inhibits GTPase activity and exerts protective effects in several disease models. However, whether dynasore can alleviate lipopolysaccharide (LPS)-induced ALI is unknown. This study investigated the effect of dynasore on macrophage activation and explored its potential mechanisms in LPS-induced ALI in vitro and in vivo.Methods: Bone marrow-derived macrophages (BMDMs) were activated classically with LPS or subjected to NLRP3 inflammasome activation with LPS+ATP. A mouse ALI model was established by the intratracheal instillation (i.t.) of LPS. The expression of PYD domains-containing protein 3 (NLRP3), caspase-1, and gasdermin D (GSDMD) protein was detected by Western blots. Inflammatory mediators were analyzed in the cell supernatant, in serum and bronchoalveolar lavage fluid (BALF) by enzyme-linked immunosorbent assays. Morphological changes in lung tissues were evaluated by hematoxylin and eosin staining. F4/80, Caspase-1 and GSDMD distribution in lung tissue was detected by immunofluorescence.Results: Dynasore downregulated nuclear factor (NF)-κB signaling and reduced proinflammatory cytokine production in vitro and inhibited the production and release of interleukin (IL)-1β, NLRP3 inflammasome activation, and macrophage pyroptosis through the Drp1/ROS/NLRP3 axis. Dynasore significantly reduced lung injury scores and proinflammatory cytokine levels in both BALF and serum in vivo, including IL-1β and IL-6. Dynasore also downregulated the co-expression of F4/80, caspase-1 and GSDMD in lung tissue.Conclusion: Collectively, these findings demonstrated that dynasore could alleviate LPS-induced ALI by regulating macrophage pyroptosis, which might provide a new therapeutic strategy for ALI/ARDS.Keywords: acute lung injury, acute respiratory distress syndrome, NLRP3 inflammasome, pyroptosis, dynasore, inflammation